Students' Academic Use of Mobile Technology and Higher-Order Thinking Skills: The Role of Active Engagement - Hye Jeong Kim; Pilnam Yi; Ji In Hong (MDPI AG, 2020)
The academic use of mobile technology engages students beyond traditional classroom contexts. Over the past few years, higher education institutions have promoted students’ learning and growth by supporting their use of mobile technology. Mobile technology offers educational possibilities that can enhance students’ growth in higher education. The aim of this study is to examine the relationship between college students’ academic use of mobile technology and higher-order thinking skills through their active engagement and learning effort. The sample consisted of 456 students at a university in South Korea, and the data were analyzed using partial least squares structural equation modeling. The results suggest that the academic use of mobile technology influences students’ higher-order thinking skills directly, in addition to their learning effort and active engagement in courses. These findings provide valuable information for higher education institutions that seek to introduce interactive and technology-integrated environments.